Subband adaptive algorithms for high-order transversal filters - Lee, Kong Aik (2008)
This thesis considers the derivation and analysis of new subband adaptive algorithms for high-order transversal filters. Subband and multirate techniques were employed in deriving adaptive filtering algorithms that are computationally efficient and possess improved convergence performances against high spectral dynamic range of the input signal. One application of interest is acoustic echo cancellation (AEC), which involves colored excitation and the modeling of long impulse response. Acoustic echo canceller finds application in hands-free telephone systems, audio or video conference systems, hearing aids, voice-control systems, and many more.